Cashless Policy and the Financial Performance of Deposit Money Banks in Nigeria - Eguavoen, Jeffrey Ogie; Oseni, Nurudeen (NIU Journal of Social Sciences, 2025)
This study empirically investigated the effect of cashless policy on the financial performance of thirteen listed deposit money banks (DMBs) in Nigeria using quarterly data covering the period 2009Q1 to 2023Q4. The study employed error correction model and multivariate OLS regression. The findings revealed that mobile banking (MOB), national electronic funds transfer (NEFT) and automated teller machine (ATM) transactions have significant impact on the financial performance of DMBs in the short-run while national electronic funds transfer (NEFT), point of sales (POS), automated teller machine (ATM), Nigerian inter-bank (NIP) transfer and web-based (WB) transactions exerts significant impact on DMBs’ financial performance in the long-run. Therefore, the study recommends among others that management of DMBs should reduce the prevalence of hacking by investing more on the security of mobile banking and other electronic payment channels and this would lead to increased customer’s satisfaction and patronage which can induce higher ROA of DMBs. Keywords: Cashless Policy, Financial Performance, Mobile Banking, Point of Sales, Automated Teller Machine.